Psychiatric and legal process in compulsory hospitalization [Zorunlu yatışlta psikiyatrik ve hukuksal süreç] - (:unkn) unknown (Istanbul Universitesi, 2013)
Objective: Compulsory hospitalization is of particular concern for psychiatrists around the world. Different practices have been adopted in various countries. The practice in this field in our country is regulated by Civil Law Article 432. In this study, our primary objective was to examine sociodemographic characteristics and psychiatric features of the patients who were subject to compulsory hospitalization in Erenkoy Mental Health Training and Research Hospital. Secondarily, we discussed the legal process for compulsory hospitalization. Method: The data of this study were gathered from 100 psychiatric patients randomly selected among those who were subject to compulsory hospitalization between 1 July 2009 and 1 July 2010. Data on the clinical features of the patients were obtained by retrospectively reviewing hospital medical records. Findings: The rate of compulsory hospitalization within the last 1 year was 23.11% in proportion to all hospitalizations. Schizophrenia (39%), bipolar disorder (27%) and schizoaffective disorder (9%) were found to be the most common diagnoses requiring compulsory hospitalization. Of the study patients, 68% were male and 32% were female; mean age was 37±8.1 years. Mean duration of hospitalization was 16±7.8 days. Discussion and Conclusion: We need to prospective studies about compulsory hospitalization and long term treatment of psychiatric patients.
Keywords: Compulsory hospitalization; Forensic psychiatry; Psychiatric patient